Nitrogen and Sulphur Fertilisation for Marketable Yields of Cabbage (Brassica oleracea L. var. Capitata), Leaf Nitrate and Glucosinolates and Nitrogen Losses Studied in a Field Experiment in Central Slovenia - Kacjan Maršić, Nina (Plants (Basel), 2021)
A field trial of white cabbage (Brassica oleracea var. Capitata L.) was carried out under the humid temperate climate conditions in Central Slovenia to investigate the effects of calcium ammonium nitrate (0, 180 and 240 kg N ha(−1)) and gypsum (0 and 40 kg S ha(−1)) fertilisation on yield, yield quality (nitrate, glucosinolate levels and glucosinolate profile) and nitrogen use efficiency. The highest marketable yield, dry matter yield and nitrogen uptake were obtained at the highest nitrogen fertilisation rate when in combination with sulphur. For this treatment, the nitrogen surplus in the soil after harvesting was lower than for the same nitrogen fertilisation without sulphur application. For the combination N(240)S(40), the sulphur addition significantly increased nitrogen use efficiency, which resulted in reduced nitrate content in the cabbage heads. The chemical forms of glucosinolates showed that 80–85% were aliphatic glucosinolates with the remainder as the indole group. For the aliphatic glucosinolates, significant interactions between nitrogen and sulphur fertilisations were reflected in increased levels of progoitrin and glucoiberin when sulphur was applied at the lower nitrogen fertilisation rates. For the indole group, the levels of glucobrassicin and the indole group itself decreased at higher nitrogen fertilisation rates, independent of sulphur fertilisation.